Features of illustrating books for children of different age groups - Bycheva, Anastasia; Galchynska, Olga; Pshinka, Natalya (Art and Design, 2026)
In the context of the rapid development of digital media and changes in visual culture, the creation of high- quality, aesthetically coherent, and psychologically grounded illustrative material becomes especially important, as it is capable of maintaining attention, fostering the development of imaginative thinking, and forming visual literacy in children of different age groups. The purpose of the work was to identify stylistic, compositional and technological features of the design of a children’s book, taking into account the age characteristics of the reader. To achieve this goal, visual-analytical, comparative-typological and system-analytical methods were used. The article investigated the main features of illustrating books for children of different ages. It was substantiated that illustrating books significantly affects the formation of the worldview of the future generation, since illustration is often the first visual experience of a child, and the perception of the surrounding world depends on its quality and content. Their influence on the content and placement of text for each age group has been determined. Special attention was paid to the peculiarities of cooperation between illustrators and editors to form a holistic image of a children’s book. The main stages of work on illustration, as well as the basic principles and significance of artistic design, were highlighted. The relevance of improving the illustrative accompaniment of children’s books as an important factor in the formation of aesthetic perception, creative thinking and reading culture in children of different ages has been investigated. Particular attention was paid to taking into account the psychological and cognitive features of children’s perception as a key task for illustrators, designers and editors working in the field of children’s book publishing. The practical value of the study lies in the development of methodological recommendations for illustrators, designers and publishers on optimising the graphic design of children’s publications in accordance with the age structure of the readership